2024
DOI: 10.1371/journal.pone.0292966
|View full text |Cite
|
Sign up to set email alerts
|

Sustained antibacterial activity of orthodontic elastomeric ligature ties coated with a novel kombucha-derived bacterial nanocellulose: An in-vitro study

Fateme Eskandari,
Susan Borzou,
Alireza Razavian
et al.

Abstract: Incipient carious lesions, the most common complication in orthodontic patients with fixed appliances, call for the development of novel preventive dental materials that do not rely on patient adherence. The present study aimed to assess the ability of elastomeric ligatures coated with bacterial nanocellulose (BNC) to deliver sustained antibacterial activity, during the standard 28-day interval between orthodontic appointments, without compromising their mechanical properties. Kombucha membrane was used to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Overall, the most recent studies offer significant insights into the use of natural products and novel materials in dentistry, emphasizing their efficacy and potential applications. Eskandari et al [ 59 ] demonstrated that elastomeric ligature ties coated with kombucha-derived bacterial nanocellulose maintain their mechanical properties while providing sustained antibacterial activity, which is crucial for preventing carious lesions in orthodontic patients. Another study [ 60 ] highlighted the broad therapeutic potential of Cissus extracts in dentistry, noting their antibacterial, anti-inflammatory, and tissue-regenerative properties, which could modernize dental practices.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the most recent studies offer significant insights into the use of natural products and novel materials in dentistry, emphasizing their efficacy and potential applications. Eskandari et al [ 59 ] demonstrated that elastomeric ligature ties coated with kombucha-derived bacterial nanocellulose maintain their mechanical properties while providing sustained antibacterial activity, which is crucial for preventing carious lesions in orthodontic patients. Another study [ 60 ] highlighted the broad therapeutic potential of Cissus extracts in dentistry, noting their antibacterial, anti-inflammatory, and tissue-regenerative properties, which could modernize dental practices.…”
Section: Discussionmentioning
confidence: 99%